Analysis of Implementing Digital Leadership Within Organizations - Veithzal, Andria Permata; Rony, Zahara Tussoleha (Dinasti International Journal of Digital Business Management, 2024)
The purpose of this scientific article is to present a comprehensive review of current scientific literature as perceived by researchers. This reflection employs a graphic writing style, wherein analysts collect the requisite data from supplementary sources prior to doing a thorough analysis and improving it accordingly. Data for study is gathered through supplementary data collection methods, which involve obtaining additional information from sources such as books, articles, research papers, lecture notes, and the Internet. The literature review involves the careful selection, examination, and revision of a collection of relevant scientific articles. The variables presented in the results and discussion section fulfill the requirement of being accountable in line with the objective of this scientific article, which is to describe and provide perspective. These variables are followed by other variables that can serve as distinguishing factors, as well as the subject of research and the model used to analyse the study's findings.